Dietary β-Carotene on Postpartum Uterine Recovery in Mice: Crosstalk Between Gut Microbiota and Inflammation - Yang, Xizi; He, Ziyu; Hu, Ruizhi; Yan, Jiahao; Zhang, Qianjin; Li, Baizhen; Yuan, Xupeng; Zhang, Hongfu; He, Jianhua; Wu, Shusong (Frontiers in Immunology, 2021)
As the precursor of vitamin A, β-carotene has a positive effect on reproductive performance. Our previous study has shown that β-carotene can increase antioxidant enzyme activity potentially through regulating gut microbiota in pregnant sows. This study aimed to clarify the effect of β-carotene on reproductive performance and postpartum uterine recovery from the aspect of inflammation and gut microbiota by using a mouse model. Twenty-seven 6 weeks old female Kunming mice were randomly assigned into 3 groups (n=9), and fed with a diet containing 0, 30 or 90 mg/kg β-carotene, respectively. The results showed that dietary supplementation of β-carotene reduced postpartum uterine hyperaemia and uterine mass index (P<0.05), improved intestinal villus height and villus height to crypt depth ratio, decreased serum TNF-α and IL-4 concentration (P<0.05), while no differences were observed in litter size and litter weight among three treatments. Characterization of gut microbiota revealed that β-carotene up-regulated the relative abundance of genera Akkermansia, Candidatus Stoquefichus and Faecalibaculum, but down-regulated the relative abundance of Alloprevotella and Helicobacter. Correlation analysis revealed that Akkermansia was negatively correlated with the IL-4 concentration, while Candidatus Stoquefichus and Faecalibaculum had a negative linear correlation with both TNF-α and IL-4 concentration. On the other hand, Alloprevotella was positively correlated with the TNF-α, and Helicobacter had a positive correlation with both TNF-α and IL-4 concentration. These data demonstrated that dietary supplementation of β-carotene contributes to postpartum uterine recovery by decreasing postpartum uterine hemorrhage and inhibiting the production of inflammatory cytokines potentially through modulating gut microbiota.